Language Style Analysis on the Character "Sophie" in the School for Good and Evil Movie - Aryani Dewi, Ni Kadek; Sulatra, I Komang (Ethical Lingua: Journal of Language Teaching and Literature, 2024)
This research aims to identify the language style and examine the social factors that influence the use of language style by the character “Sophie” in The School for Good and Evil movie. This is qualitative research since the data are in the form of utterances spoken by Sophie. The data of this study were collected by observation method thorough. Data was collected by watching the movie and classifying the utterances according to the type of language style. The collected data were analysed by employing the theory by Joss (1967) regarding the type of language style and the theory from Holmes (2013) to examine the factors. This study shows that Sophie uses four types of language styles in the movie: casual style, formal style, consultative style, and intimate style. The casual style was the most predominant data (31%) because Sophie dominantly talked to her friends casually. Moreover, this study examines Sophie's choice of language style in the movie The School for Good and Evil is affected by four factors: the participants, setting, topic, and function.